Acceptance sampling in quality control: from theory to the web in PHP, python, and gnuplot - Casquilho, Miguel (2023)
Quality is nowadays a ubiquitous component in manufacturing and many other activities. We present a computation related to Acceptance Sampling, which, together with Statistical Process Control, makes the fundamentals of statistical Quality Control. We provide a webpage where a user’s typical sample from a process can be inserted, leading to “accept” or “reject” vs. given specifications. We have several goals: to offer, on a webpage, the statistical procedure computation, which is otherwise complex; to combine, on a Linux platform, programming languages, PHP and Python, and a graphical utility, gnuplot; and to stress the suggestion of the Web as a computing medium. The webpage is freely accessible to a user just using a browser, i.e., installing no software, thus needing no special power or matching operating system, this being an example adaptable to many other problems. The study also draws attention both to the use of the Web for scientific computing, and to the convenience of this use in scientific publications. Web-based computing in general is advocated, this route uses the same executable programs as classical computing, which is the core technical difficulty. In our technological era, this still insufficiently explored approach is here made accessible, inviting the sharing between academia and industry.